Sources and health risks of heavy metal(loid) contamination in farmland near Shanxi coal mines - Li Cao; Li Cao; Li Cao; Li Cao; Huirong Duan; Huirong Duan; Bijun Cheng; Bijun Cheng; Qianying Xiang; Qianying Xiang; Shuhan Wang; Shuhan Wang; et al. (Frontiers in Soil Science)
Heavy metal(loid) contamination in farmlands around coal mining areas significantly threatens ecosystem stability and human health. In this study, the extent and sources of heavy metal(loid) contamination in farmland near Shanxi coal mines were assessed using the absolute principal component scores-multiple linear regression (APCS-MLR) model. Additionally, a probabilistic health risk assessment model was developed using Monte Carlo simulation to determine the health risks faced by local residents. The average concentrations of soil Pb, Hg, Mn, and Zn was 28.56mg/kg, 0.17mg/kg, 666.29mg/kg, and 83.49mg/kg, respectively. In maize, Pb, Zn, and Cr concentrations exceeded their respective safety thresholds, with exceedance occurrence rates of 16.67%, 95.83%, and 100%, respectively. Among them, Cr exhibited the highest bioaccumulation factor (BCF), reaching 0.55 in maize. Five main sources of soil heavy metal(loid) contamination were identified: coal mining activities, air pollution, agricultural practices, natural sources, and coal combustion. Probabilistic health risk assessment revealed that the average non-carcinogenic hazard index (HI) values of soil-mediated heavy metal(loid) exposure remained below 1 for both children and adults, although the average HI for children was 2.96 times higher than adults. However, the average HI of maize-mediated heavy metal(loid) exposure exceeded the risk threshold, reaching 1.44 for children and 1.27 for adults. In contrast, the overall carcinogenic risk (CR) of maize-mediated heavy metal(loid) was 3.71 times higher in adults than in children. In conclusion, the farmland near Shanxi coal mines was severely contaminated with heavy metal(loid)s, with coal mining activities being the main pollution source. Local residents, particularly children, faced substantial health threats.